Maternal and birth cohort studies in the Gulf Cooperation Council countries: protocol for a systematic review and narrative evaluation. Issue 1 (27th January 2018) - Al-Rifai, Rami H.; Ali, Nasloon; Barigye, Esther T.; Al Haddad, Amal H. I.; Loney, Tom; Al-Maskari, Fatima; Ahmed, Luai A.
Abstract : Introduction: Cohort studies have revealed that genetic, socioeconomic, communicable and non-communicable diseases, and environmental exposures during pregnancy may influence the mother and her pregnancy, birth delivery and her offspring. Numerous studies have been conducted in the Gulf Cooperation Council (GCC) countries to examine maternal and birth health. The objectives of this protocol for a systematic review are to systematically review and characterise the exposures and outcomes that have been examined in the mother and birth cohort studies in the GCC region, and to summarise the strength of association between key maternal exposures during pregnancy (ie, body mass index) and different health-related outcomes (ie, mode of birth delivery). The review will then synthesise and characterise the consequent health implications and will serve as a platform to help identify areas that are overlooked, point out limitations of studies and provide recommendations for future cohort studies. Methods and analysis: Medline, Embase, Cochrane Library and Web of Science electronic databases will be comprehensively searched. Two reviewers will independently screen each study for eligibility, and where discrepancies arise they will be discussed and resolved; otherwise a third reviewer will be consulted. The two reviewers will also independently extract data into a predefined Excel spreadsheet. The included studies will be categorised on the basis of whether the participant is a mother, infant or mother–infant dyad. Outcome variables will be divided along two distinctions: mother or infant. Exposure variables will be divided into six domains: psychosocial, biological, environmental, medical/medical services, maternal/reproductive and perinatal/child. Studies are expected to be of heterogeneous nature; therefore, quantitative syntheses might be limited. Ethics and dissemination: There is no primary data collection; therefore, ethical review is not necessary. The findings of this review will be disseminated in a peer-reviewed journal and presented at relevant conferences. PROSPERO registration number: CRD42017068910.